2024
DOI: 10.1007/s00027-023-01039-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved greenhouse gas (CO2, CH4, and N2O) emissions from highland lakes of the Andes cordillera in Northern Ecuador

Gonzalo Chiriboga,
Steven Bouillon,
Alberto V. Borges

Abstract: We report, in 15 Ecuadorian mountainous lakes, dissolved concentrations of CO 2 , CH 4 , and N 2 O and a suite of ancillary biogeochemical variables (dissolved inorganic nutrients, oxygen, major cations, dissolved and particulate organic carbon, and the stable isotope composition of dissolved inorganic carbon and water). The sampled lakes were located in the páramos of Salve Facha and Antisana y Mojanda (northern region of Ecuadorian Andes), along an elevational gradient from 2213 to 4361 m above sea level, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
0
0
Order By: Relevance
“…6E). Several studies reported a negative correlation between CH4 concentration and lake size (surface and/or depth) across spatial scales (local to global) (Borges et al, 2011;Kankaala et al, 2013;Holgerson and Raymond, 2016;Borges et al, 2022;Chiriboga et al 2024), yet one study reported no relationship (Peacock et al, 2019) and another a positive correlation (Rabaey et al, 2022). The positive relationship between CH4 concentration and pond size in the ponds of the city of Brussels was probably indirect and reflected another driver.…”
Section: Spatial Variations In Ghgsmentioning
confidence: 99%
See 1 more Smart Citation
“…6E). Several studies reported a negative correlation between CH4 concentration and lake size (surface and/or depth) across spatial scales (local to global) (Borges et al, 2011;Kankaala et al, 2013;Holgerson and Raymond, 2016;Borges et al, 2022;Chiriboga et al 2024), yet one study reported no relationship (Peacock et al, 2019) and another a positive correlation (Rabaey et al, 2022). The positive relationship between CH4 concentration and pond size in the ponds of the city of Brussels was probably indirect and reflected another driver.…”
Section: Spatial Variations In Ghgsmentioning
confidence: 99%
“…The levels of CO2 and CH4 in lakes vary as a function of lake size (Lapierre and del Giorgio, 2012;Kankaala et al, 2013;Raymond et al, 2013;Holgerson and Raymond, 2016;Casas-Ruiz et al, 2021;Borges et al, 2022;Chiriboga et al 2024) as well as land cover (Maberly et al, 2013). Combined lake size and land cover determine relative levels of allochthonous organic matter inputs to aquatic systems and the general balance of autotrophy and heterotrophy largely determining CO2 levels (del Giorgio and Peters, 1994), as well as benthic methanogenesis.…”
Section: Spatial Variations In Ghgsmentioning
confidence: 99%